Effective Strategies for Implementing Remedial and Enrichment Learning Activities in Elementary Schools: A Literature Study - Zahra Meida Lutfiah; Citra Suci Ramadani; Khaira Laini Zahra; Rahmilawati Ritonga (AMK : Abdi Masyarakat UIKA, 2026)
Remedial and enrichment activities in elementary schools are an important step to ensure that every student has the opportunity to learn according to their abilities and needs. Through a literature study, this study summarizes various findings from journals, books, and research reports to capture how the concepts, implementation processes, challenges, and effective strategies of remedial and enrichment are applied at the basic level. The results of the study show that the most decisive initial step is to recognize students' learning difficulties through initial assessments, classroom observations, and portfolio analysis. In remedial activities, teachers need to develop a targeted improvement plan, utilize concrete media, provide guidance in small groups or through peer tutors, and conduct reassessments to see student progress. Meanwhile, enrichment can be provided by identifying students who demonstrate higher abilities, then engaging them in creative projects, mini-research, or interest-based activities that challenge higher-level thinking skills. Teachers play a very strategic role as planners, facilitators, as well as providers of emotional support. In the field, the implementation of these two programs is still constrained by limited time, large number of students, and lack of supporting resources. Therefore, strategies such as differentiated learning, the use of simple technology, and the implementation of project-based learning are recommended to increase effectiveness. This study is expected to be a practical reference for elementary school teachers in developing remedial and enrichment programs that are more adaptive, inclusive, and sustainable.